Thoracic aorta cardiac-cycle related dynamic changes assessed with a 256-slice CT scanner - Carrascosa, Patricia (2013)
Objective: The aim of our study was to demonstrate whether the dynamic changes previously documented at the ascending and abdominal aorta are replicated at the thoracic aorta. Methods and results: A consecutive series of thirty patients referred to our institution to undergo CT angiography of the thoracic aorta (CTA) constituted the study population. Patients with diffuse aortic atherosclerosis were excluded from the analysis. All studies were acquired with a 256-MDCT scanner and ECG-gating was performed in all cases. Two orthogonal imaging planes (maximal and minimal diameters) were obtained at three different levels of the descending thoracic aorta, using the distance from the left subclavian artery as proximal landmark: 10, 40, and 80 mm distance. The mean age was 58.9±15.7 years and 16 (53%) patients were male. Descending aorta measurements at 10, 40, and 80 mm distance from the left subclavian artery were all significantly larger within the systolic window (P<0.01 for all comparisons). Measurements of the maximal diameter were systematically larger than the minimal diameters among all aortic positions including ungated, systolic, and diastolic measurements (P<0.05 for all comparisons). Conclusions: The main finding of our pilot investigation was that the thoracic descending aorta undergoes significant conformational changes during the cardiac cycle, irrespective from the distance from the left subclavian artery.